Bride Kidnapping as a Marriage Tradition: An Examination of Newcomers' Perspectives on Merariq in Lombok Island - Nova Apriliani; Deviana Mayasari; Aliahardi Winata; Ravindra Ashok Jadhav (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The merariq tradition constitutes a significant cultural practice prevalent among many members of the Sasak community in Lombok, with historical roots extending back to ancient times. This tradition has been meticulously preserved and conveyed through generations, reflecting the unique cultural heritage of the Sasak people. Within the framework of this research, religious norms pertain to the behavioral regulations that are derived from the sacred texts of various religions. These norms guide followers in their moral and ethical conduct. Conversely, ethical norms are dictated by individual conscience, providing a subjective basis for discerning right from wrong. The primary objective of this study is to examine the perspectives of newcomers visiting Lombok regarding the merariq tradition, particularly in relation to established religious and ethical norms within the Sasak community. This research adopts a qualitative methodology, specifically utilizing a descriptive qualitative approach. The findings indicate that, from the viewpoint of these outsiders, the merariq tradition does not infringe upon either religious or ethical norms. This conclusion is noteworthy, as it is evident that there are no explicit written regulations within the frameworks of religious or ethical guidelines that directly prohibit the observance of the merariq tradition. This understanding underscores the perspective that an action is generally regarded as a violation of established norms only in the presence of clear prohibitory rules. Consequently, for these visitors, the merariq tradition is perceived as a respected cultural expression that integrates harmoniously within the broader social and religious context of Lombok.